Chest-Worn Health Monitor Based on a Bistatic Self-Injection-Locked Radar - Wang, Fu-Kang; Chou, You-Rung; Chiu, Yen-Chen; Horng, Tzyy-Sheng (IEEE transactions on biomedical engineering, 2015)
This paper presents wearable health monitors that are based on continuous-wave Doppler radar technology. To achieve low complexity, low power consumption, and simultaneous wireless transmission of Doppler information, the radar architecture is bistatic with a self-injection-locked oscillator (SILO) tag and an injection-locked oscillator (ILO)-based frequency demodulator. In experiments with a prototype that was operated in the medical body area network and the industrial scientific and medical bands from 2.36 to 2.484 GHz, the SILO tag is attached to the chest of a subject to transform the movement of the chest due to cardiopulmonary activity and body exercise into a transmitted frequency-modulated wave. The tag consumes a very low power of 4.4 mW. The ILO-based frequency demodulator, located 30 cm from the subject, receives and processes this wave to yield the waveform that is associated with the movement of the chest. Following further digital signal processing, the cardiopulmonary activity and body exercise are displayed as time-frequency spectrograms. Promisingly, the experimental results that are presented in this paper reveal that the proposed health monitor has high potential to integrate a cardiopulmonary sensor, a pedometer, and a wireless transmission device on a single radar platform.